2020
DOI: 10.3390/plants9111417
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry FaNAC2 Enhances Tolerance to Abiotic Stress by Regulating Proline Metabolism

Abstract: The quality and yields of strawberry plants are seriously affected by abiotic stress every year. NAC (NAM, ATAF, CUC) transcription factors are plant-specific, having various functions in plant development and response to stress. In our study, FaNAC2 from strawberry (Fragaria × ananassa, cultivar “Benihoppe”) was isolated and found to be a member of the ATAF sub-family, belonging to the NAC family of transcription factors. FaNAC2 was strongly expressed in the shoot apical meristem and older leaves of strawberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that multiple NAC members are involved in the formation of organ boundaries and meristems, such as NAM in Petunia (Souer et al., 1996), CUC1‐3 in Arabidopsis (Aida et al., 1997; Raman et al., 2008; Vroemen et al., 2003) and CUP in Antirrhinum majus (Weir et al., 2004). Studies on FaNAC2 homologs in other species and in strawberry have focused on its role in resistance to biotic and abiotic stresses, such as ATAF1 in Arabidopsis, OsNAC6 in rice and FaNAC2 in strawberry (Liang et al., 2020; Nakashima et al., 2007; Wu et al., 2009). In this study, we found for the first time that FaNAC2 was involved in runner formation and could directly activate FaHAN by binding to its promoter (Figures 6a and 7f).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that multiple NAC members are involved in the formation of organ boundaries and meristems, such as NAM in Petunia (Souer et al., 1996), CUC1‐3 in Arabidopsis (Aida et al., 1997; Raman et al., 2008; Vroemen et al., 2003) and CUP in Antirrhinum majus (Weir et al., 2004). Studies on FaNAC2 homologs in other species and in strawberry have focused on its role in resistance to biotic and abiotic stresses, such as ATAF1 in Arabidopsis, OsNAC6 in rice and FaNAC2 in strawberry (Liang et al., 2020; Nakashima et al., 2007; Wu et al., 2009). In this study, we found for the first time that FaNAC2 was involved in runner formation and could directly activate FaHAN by binding to its promoter (Figures 6a and 7f).…”
Section: Discussionmentioning
confidence: 99%
“… 53 In plants, studies on NAC gene regulation in response to drought, salinity, low-temperature, high-temperature, heavy metals, disease, and other stresses have been published. 54–59 However, few reports about SsNAC genes involved in responses to biotic and abiotic stresses are available. Therefore, this study further analyzed the expression patterns and potential functions of 12 SsNAC genes in response to various biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transgenic rice overexpressing ONAC022 are more tolerant to drought and salt stress (Hong et al 2016). The strawberry FaNAC2 gene could be signi cantly induced by cold, salt and drought stresses, and transgenic tobacco expressing FaNAC2 showed increased resistance to cold and salt stresses (Liang et al 2020). Di19 proteins are a subset of the Cys2/His2 zinc nger protein family, which plays an important role in regulating multiple stress responses (Milla et al 2006;Qin et al 2014).…”
Section: Discussionmentioning
confidence: 99%